CREATION OF BIOLOGICAL DATABASES USING OBJECT-ORIENTED SYSTEM ANALYSIS - O. M. Klyuchko; L. P. Buchatsky; O. V. Melezhyk (Biotechnologia Acta, 2019)
The aim of the work was to develop electronic database of biological organisms (fishes, viruses) on the base of the methods that have been used before in mathematics, engineering, physics. The methods of object-oriented system analysis, construction of models of subject spaces (problem space, solution space), ER-diagrams, of constructing databases and others were applied. The examples of prototypes of modern databases with information about fishes developed over the past years in Western European and American countries were presented. An overview of applied methods, concepts and terminology from the areas of object-oriented system analysis, database designing was disclosed. In conclusions the description of constructed database and practical recommendations for the development of databases with the information about domestic biological organisms for electronic information systems are given.